2016
DOI: 10.14503/thij-15-5046
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Takotsubo Cardiomyopathy Related to Recurrent Thyrotoxicosis

Abstract: Takotsubo cardiomyopathy, or transient left ventricular apical ballooning syndrome, is characterized by acute left ventricular dysfunction caused by transient wall-motion abnormalities of the left ventricular apex and mid ventricle in the absence of obstructive coronary artery disease. Recurrent episodes are rare but have been reported, and several cases of takotsubo cardiomyopathy have been described in the presence of hyperthyroidism. We report the case of a 55-year-old woman who had recurrent takotsubo card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…The endothelial dysfunction typically persists for only a few weeks after an episode of TC, and it responds to specific therapy involving nitrates, calcium antagonists, and possibly L-arginine. 2,3 Like Patel and colleagues, 1 we emphasize the importance of prospective and safe mechanistic investigations in the quest to clarify the nature of TC.…”
Section: Takotsubo Cardiomyopathymentioning
confidence: 83%
See 1 more Smart Citation
“…The endothelial dysfunction typically persists for only a few weeks after an episode of TC, and it responds to specific therapy involving nitrates, calcium antagonists, and possibly L-arginine. 2,3 Like Patel and colleagues, 1 we emphasize the importance of prospective and safe mechanistic investigations in the quest to clarify the nature of TC.…”
Section: Takotsubo Cardiomyopathymentioning
confidence: 83%
“…Establishing Diagnosis and Causes through Prospective Testing T he accompanying case report by Patel and colleagues 1 concerns recurrent takotsubo cardiomyopathy (TC) in the context of hyperthyroidism's onset. The authors deserve compliments on their interesting article and their correct phenotypic diagnosis of both TC and hyperthyroidism.…”
Section: Takotsubo Cardiomyopathymentioning
confidence: 99%
“…[7][8][9][10] The possible relationship between dilated cardiomyopathy, Takotsubo cardiomyopathy, and Graves' disease is reported in the literature. 11,12 Hübner et al experimentally revealed impairment of cardiac performance in both adolescent and adult mice with Graves' disease. The cardiac performance could be partly restored by early hormonal treatment, but adult mice lacked this recovery potential.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of thyroid hormones cause exaggerated inotropic and chronotropic responses to catecholamines. There is over-regulation of beta-adrenergic receptors by thyroid hormones in many tissues, including the heart [ 8 , 19 21 ].…”
Section: Discussionmentioning
confidence: 99%